2015
DOI: 10.1111/nmo.12504
|View full text |Cite
|
Sign up to set email alerts
|

Digestive, cognitive and hedonic responses to a meal

Abstract: When appropriate conditions are met, the response to a meal includes a hedonic dimension involving pleasant sensation of digestive well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(77 citation statements)
references
References 25 publications
3
71
2
Order By: Relevance
“…In this study, satiation was not specifically measured, and among the choices in the perception questionnaire, subjects reported by‐and‐large pressure/bloating sensation. In a recent study using another test meal, 20 satiation was also scored on a separate scale, and we found that it tightly paralleled pressure/bloating scores (unpublished data). Furthermore, in this study, the responses were similar whether the predominant sensation was pressure/bloating or not.…”
Section: Discussionmentioning
confidence: 51%
“…In this study, satiation was not specifically measured, and among the choices in the perception questionnaire, subjects reported by‐and‐large pressure/bloating sensation. In a recent study using another test meal, 20 satiation was also scored on a separate scale, and we found that it tightly paralleled pressure/bloating scores (unpublished data). Furthermore, in this study, the responses were similar whether the predominant sensation was pressure/bloating or not.…”
Section: Discussionmentioning
confidence: 51%
“…In previous studies, broth ingestion under these conditions induced satiation and satisfaction; however, satiation after the probe meal in the current study had a negative hedonic dimension with decrease in digestive well‐being despite the fact that discomfort was negligible. A similar dissociated response, i.e., satiation and dissatisfaction, was observed in the previous studies with experimental gastric distension inducing fullness sensation . The meal load in the present study was considerably larger than in previous tests with a regular broth serving; however, well‐being already decreased during ingestion.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, changes in the late lipidic response to the meal were related to digestive well‐being and reduced desire of eating a food of choice. Previous studies showed that lipid meals improve mood and that infusion of lipid directly into the small bowel induces pleasant fullness sensation, i.e., satiation associated to digestive well‐being …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations